Off-label infusion of biosimilar bevacizumab: A provincial experience. (October 2020) - Geirnaert, Marc; Howarth, Jacy; Kellett, Curtis; Martin, Kristen; Streilein, Scott; Ricard, Chad; Wasney, Danica; Niraula, Saroj
The product monograph for reference bevacizumab (Avastin) and biosimilar bevacizumab (Mvasi) recommend to infuse the first dose of bevacizumab over 90 min, second dose over 60 min and third and subsequent doses over 30 min. Despite the product monograph recommendations, many institutions adopted an accelerated bevacizumab (Avastin) 0.5 mg/kg/min infusion time. Our province adopted the accelerated infusion time at time of biosimilar bevacizumab (Mvasi) adoption. Our experience with the accelerated infusion time was well tolerated in the first five months of biosimilar bevacizumab adoption across different tumor types.